Local existence and blow up of solutions to a logarithmic nonlinear wave equation with delay. Issue 3 (17th February 2020) - Kafini, Mohammad; Messaoudi, Salim
ABSTRACT: This paper is concerned with a problem of a logarithmic nonlinear wave equation with delay. The local existence result has been established using the semigroup theory. In addition, for negative initial energy, a finite-time blow-up result is proved.